2000
DOI: 10.1096/fasebj.14.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal determination of skin collagen glycation and glycoxidation rates predicts early death in C57BL/6NNIA mice

Abstract: In 1988, the National Institute on Aging launched a 10-year program aimed at identification of biomarkers of aging. Previous results from our laboratory showed that pentosidine, an advanced glycation product, formed in skin collagen at a rate inversely related to maximum life span across several mammalian species. As part of the Biomarkers Program, we investigated the hypothesis that longitudinal determination of glycation and glycoxidation rates in skin collagen could predict longevities in ad libitum-fed (AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 53 publications
5
48
0
1
Order By: Relevance
“…Furthermore, the present data suggest that the rate of a generally occurring aging process (i.e., AGE formation occurs in all tissue but is especially important in tissue with slow turnover, such as articular cartilage [18]) may predispose to the development of an agerelated pathology such as OA. These data are consistent with the observations of Sell et al (57,58), who showed an inverse relationship between the rate of glycation and the longevity of a species, which further supports the idea that AGE accumulation is an important process in aging and age-related diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the present data suggest that the rate of a generally occurring aging process (i.e., AGE formation occurs in all tissue but is especially important in tissue with slow turnover, such as articular cartilage [18]) may predispose to the development of an agerelated pathology such as OA. These data are consistent with the observations of Sell et al (57,58), who showed an inverse relationship between the rate of glycation and the longevity of a species, which further supports the idea that AGE accumulation is an important process in aging and age-related diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Statistical analysis was performed according to methods previously described in detail in (25). In brief, statistical significance of differences in mean values was assessed by repeated-measures ANOVA or Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Insoluble Collagen-Insoluble collagen was prepared as detailed previously (2,12). In brief, samples were delipidated, extracted with 1 M sodium chloride and 0.5 M acetic acid, digested with 0.1% pepsin in 0.5 M acetic acid at 4°C, and freeze-dried (2).…”
Section: Methodsmentioning
confidence: 99%
“…Statistical Analyses-Statistical methods including regression, correlation, and analysis of variance were performed as described previously by us (12,14,15) using SPSS software (SPSS Inc., Chicago, IL). Race, gender, presence of diabetes (type 1 and type 2), chronic renal disease, and ESRD were independent variables (16).…”
Section: Enzymatic Digestion Of Insolublementioning
confidence: 99%